O‐(Triazolyl)methyl Carbamates as a Novel and Potent Class of Fatty Acid Amide Hydrolase (FAAH) Inhibitors. Issue 2 (22nd October 2014) - Colombano, Giampiero; Albani, Clara; Ottonello, Giuliana; Ribeiro, Alison; Scarpelli, Rita; Tarozzo, Glauco; Daglian, Jennifer; Jung, Kwang‐Mook; Piomelli, Daniele; Bandiera, Tiziano
Abstract Inhibition of fatty acid amide hydrolase (FAAH) activity is under investigation as a valuable strategy for the treatment of several disorders, including pain and drug addiction. A number of potent FAAH inhibitors belonging to different chemical classes have been disclosed to date; O‐aryl carbamates are one of the most representative families. In the search for novel FAAH inhibitors, a series of O‐(1, 2, 3‐triazol‐4‐yl)methyl carbamate derivatives were designed and synthesized exploiting a copper‐ catalyzed [3+2] cycloaddition reaction between azides and alkynes (click chemistry). Exploration of the structure–activity relationships within this new class of compounds identified potent inhibitors of both rat and human FAAH with IC50 values in the single‐digit nanomolar range. In addition, these derivatives showed improved stability in rat plasma and kinetic solubility in buffer with respect to the lead compound. Based on the results of the study, the novel analogues identified can be considered to be promising starting point for the development of new FAAH inhibitors with improved drug‐like properties.